A Cyclization–Rearrangement Cascade for the Synthesis of Structurally Complex Chiral Gold(I)–Aminocarbene Complexes1. (7th July 2014) - Kolundžić, Filip; Murali, Annamalai; Pérez‐Galán, Patricia; Bauer, Jonathan O.; Strohmann, Carsten; Kumar, Kamal; Waldmann, Herbert
Abstract A facile synthesis of chiral cyclic alkyl aminocarbene–gold(I) complexes from gold‐free 1, 7‐enyne substrates was developed. The novel cyclization–rearrangement reaction sequence is triggered by the addition of (Me2S)AuCl to different 1, 7‐enynes and leads to structurally unique carbene–gold(I) complexes in high yields. These novel complexes are catalytically active and inhibit the proliferation of different human cancer cell lines.